1996
DOI: 10.1002/(sici)1097-4628(19960207)59:6<937::aid-app5>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Heat effects in sorption of organic vapors in rubbery polymers

Abstract: SYNOPSISDuring supposedly isothermal sorption/desorption of gases or vapors by solid polymers, latent heat effects alter local temperatures with the result that diffusion behavior may appear to be non-Fickian. Even when sorption curves are seemingly Fickian, spurious values of the diffusion coefficient, D, may still be inferred. These phenomena are examined in an experimental and theoretical study of incremental sorption/desorption of acetone vapor in the fluoroelastomer, vinylidene fluoride/hexafluoropropylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Therefore, the driving potential for bulk transport of water molecules from the air to the wood is decreased locally. The effect of temperature changes during sorption has been suggested from several studies of sorption in various materials [64,65], where the approach to equilibrium was slower than predicted by a Fickian diffusion model, see Section 5.1. Moreover, the shape of the sorption curves did not correspond to the Fickian diffusion model.…”
Section: Temperature Changementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the driving potential for bulk transport of water molecules from the air to the wood is decreased locally. The effect of temperature changes during sorption has been suggested from several studies of sorption in various materials [64,65], where the approach to equilibrium was slower than predicted by a Fickian diffusion model, see Section 5.1. Moreover, the shape of the sorption curves did not correspond to the Fickian diffusion model.…”
Section: Temperature Changementioning
confidence: 99%
“…Moreover, the shape of the sorption curves did not correspond to the Fickian diffusion model. The experimental data could be explained by taking into account the increase in temperature during sorption and subsequent thermal equilibration [64][65][66]. Importantly, the sorption process was retarded by the temperature changes occurring but followed the thermal equilibration, meaning that equilibrium for both solvent uptake and temperature with the surrounding atmosphere was completed within the same timeframe.…”
Section: Temperature Changementioning
confidence: 99%
See 1 more Smart Citation
“…However, it is only recently that similar non‐Fickian effects in the sorption of organic vapors in polymer films have been attributed to nonisothermal diffusion conditions 2. The direct observation of the temperature increase accompanying the sorption of acetone in Fluorel, determined as part of this study, was reported in a prior publication 3. The present report is concerned with an attempt to interpret the sorption and diffusion results as a key to understanding the differences in the properties of the two fluoroelastomer samples.…”
Section: Introductionmentioning
confidence: 71%
“…Further, the model involved a linear approximation to determine solubility change with temperature. Another study has been conducted to assess these effects [8], and the results of this study indicate that heat effects are extremely important during sorption in polymeresolvent systems. Further, they concluded that sigmoidal uptake curves commonly result from heat effects alone in typical gravimetric experiments.…”
Section: Introductionmentioning
confidence: 99%